ASSOCIATION OF TOTAL ELECTRON CONTENT (TEC) AND F0F2 VARIATIONS WITH EARTHQUAKE EVENTS AT THE ANOMALY CREST REGION - Devi M.; Barbara A.K.; Depueva A. (My University, 2004)
The paper attempts to identify ionospheric parameters in association with earthquake at anomaly crest station through VHF Radio Beacon data and ground based ionosonde measurements while the Total Electron Content(TEC) parameters from RB observations are based mainly on data taken over Guwahati (26.2°N, 91.75° E), foF2 data used in the analysis were collected at Ahmadabad (23.01°N, 72.36°E). The paper describes methods and techniques adopted to examine modifications on these parameters if any, due to earthquake preparatory processes at equatorial anomaly crest stations. The mechanism of inducement of density changes in the ionosphere is sought through the generation of strong fountain effect possibly by the development of electric field during the earthquake preparatory process.